(untitled) (Studia austriaca, 2012)
Stauffer-Bern’s biography by Otto Brahm can be regarded as an important source for Titorelli, the painter in Kafka’s novel Der Prozeß. The way in which Kafka used this source recalls the idea of “lethetic Reading”, which Clayton Koelb introduces in order to explain the relationship between Kafka’s text Das Schweigen der Sirenen and Homer’s episode in The Odyssey. Although Kafka may have used Stauffer-Bern as a basis for his own creation, he used only a few of the details he found in Brahm’s biography. The importance of this source can then be appreciated only if we consider the story of Stauffer as the missing link between Titorelli and Kafka’s later creation of Gracchus.